Investigation of Multilayers in Polar Mesospheric Summer Echoes - Jozwicki, Dorota Sofia (UiT Norges arktiske universitet, 2025)
Understanding the influence of the Sun and space on the Earth's atmosphere is of current interest, as it may be valuable in the context of global climate change research. Polar Mesospheric Summer Echoes (PMSE) are phenomenona that rely on the presence of ice particles, offering insights into the mesosphere's temperature and water vapor content. This thesis aimed to investigate PMSE in the upper atmosphere using the EISCAT VHF radar data, with a focus on quantifying PMSE multilayers during solar maximum and solar minimum. To achieve this, a random forests-based model was used to segment PMSE data within the radar observations. This model allowed for a finer exploration of PMSE multilayers and was applied to investigate the multi-layered PMSE structures during different phases of the solar cycle, and under varying ionospheric conditions. The output of the model enabled segmentation of PMSE data with reduced back-scattered power threshold filtering, preserving a larger number of valuable data points compared to previous studies. This approach enabled the examination of both monolayer and multilayer PMSE structures in finer detail. Notably, during solar maximum, PMSE demonstrated higher average altitude, echo power, and layer thickness compared to solar minimum. Analysis of individual layers in multilayer sets shows that the altitude of the first, second, and third highest layers increases with the number of layers. Additionally, the altitude of the the lowest layer generally matched with the altitude of noctilucent clouds (NLC), as reported by observers. These clouds are visible due to light scattering off their ice particles. Furthermore, a positive correlation between echo power and ionospheric electron density at 92 km altitude above PMSE was observed. This indicates that higher electron densities might be essential for the observation of multi-layered PMSE. Looking ahead, future studies could explore the links between multi-layered PMSE formation, winds, and gravity waves. Future research could also focus on ...